THE EVALUATION OF THE SOCIOECONOMIC - MARUBINI, MBEREGENI MICHAEL (My University, 2011)
The study was conducted in Alexandra, Gauteng Province of South Africa. It is an exploratory – descriptive study. Respondents in this study included social workers in Foster Care Placements, foster parents, and foster children who have already reached 18 years of age. The key findings of this study are as follows: · The current foster care arrangements are ineffective and unsustainable. · Foster children do not benefit from placement in the way the Act intends. · Social workers in foster care placements do not provide professional assistance as stipulated in the Act. · Foster parents are not trained parental skills to enable foster children to be self reliant. · Dissemination of information around foster care is poor. · Lack of integration of services among government departments hampers sustainability
MM - P&DM
Keywords: Foster care placements; Socio-economic impacts